2014
DOI: 10.1097/hcr.0000000000000026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Outpatient Cardiac Rehabilitation Program on Clinical and Analytical Variables in Cardiovascular Disease

Abstract: Cardiac rehabilitation is an appropriate program for the improvement of clinical and analytical variables, such as functional capacity, carbohydrate and lipid metabolism, anthropometric measures, and diet. However, 12 months later, many of these benefits either remained stable or worsened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Other studies utilizing a standard CR exercise training protocol provide further evidence that when BWL is delivered in the CR setting 5 to 6 kg of weight loss is accomplished 4, 2225 (Table 1). In contrast, less than 2 kg of weight loss is observed when a BWL intervention is not employed 2630 . While demonstrating promise, additional study of the optimal dose of exercise and best methods to deliver BWL programming in the CR setting is still needed.…”
mentioning
confidence: 98%
“…Other studies utilizing a standard CR exercise training protocol provide further evidence that when BWL is delivered in the CR setting 5 to 6 kg of weight loss is accomplished 4, 2225 (Table 1). In contrast, less than 2 kg of weight loss is observed when a BWL intervention is not employed 2630 . While demonstrating promise, additional study of the optimal dose of exercise and best methods to deliver BWL programming in the CR setting is still needed.…”
mentioning
confidence: 98%
“…In a study on 59 patients who participated in a standard cardiac rehabilitation program and were re-assessed 12 months after completion of the program, it was shown that exercise tolerance time and METs achieved were significantly improved [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bioelectrical impedance analysis is valid and reliable for body composition measurement in healthy older women, 19 as well as those with HD, 20,21 and has previously been used to assess changes in body composition during CR. 22,23 In addition, it is recognized as an appropriate diagnostic tool for sarcopenia in older adults. 24 For bioelectrical impedance analysis, participants were asked to lie supine on a flat surface for ≥5 min with all extremities extended, feet apart, and hands away from their sides.…”
Section: Methodsmentioning
confidence: 99%